The Nature of Technological Change: Its Implications for Work and Labour Regulation - Smith, A.E. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
This paper applies an analytical framework which, in contrast to most recent research, takes into account the independent influence of the characteristics and capabilities of new technologies. Drawing on evidence from a survey of 435 firms in Atlantic Canada, it concludes that an analysis of the independent influence of technology is a necessary compliment to an examination of the way outcomes of change are a product of choice and negotiation.